The Effect of Webtoon-Based Reading on EFL Students’ Reading Comprehension and Reading Anxiety - Siswoyo, Dwi Nur; Wandira, Septiana (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
Reading comprehension and reading anxiety remain persistent challenges among senior high school students learning English as a Foreign Language (EFL), particularly when instruction relies heavily on traditional text-only materials. In the Indonesian EFL context, limited contextual support often contributes to students’ difficulty in understanding texts and increased anxiety. This study investigates the effect of picture-based digital media, specifically the Webtoon application, on improving reading comprehension and reducing reading anxiety among senior high school EFL students. A quasi-experimental design with a pre-test–post-test control group was employed. Fifty-six students were divided into an experimental group receiving Webtoon-based reading instruction and a control group using conventional text-based materials. Data were collected using a reading comprehension test and the Foreign Language Reading Anxiety Scale (FLRAS). Statistical analyses included independent-samples t-tests, paired-samples t-tests, and analysis of covariance (ANCOVA). The results showed that the experimental group achieved a significantly higher post-test mean score in reading comprehension (M = 85.71, SD = 7.29) than the control group (M = 77.50, SD = 7.87), t(54) = 4.049, p < 0.001. ANCOVA confirmed that the instructional method remained a significant predictor after controlling for pre-test scores. Additionally, students in the experimental group experienced a significant reduction in reading anxiety, with FLRAS scores decreasing from pre-test (M = 58.2) to post-test (M = 46.7), t(27) = 6.35, p < 0.001. These findings indicate that Webtoon-based reading instruction functions as both a cognitive and affective scaffold, enhancing comprehension while reducing reading anxiety in EFL classrooms.